Food-Grade Saponin Extract as an Emulsifier and Immunostimulant in Emulsion-Based Subunit Vaccine for Pigs - Yulia Burakova; Rachel Madera; Lihua Wang; Sterling Buist; Karen Lleellish; John R. Schlup; Jishu Shi (Journal of Immunology Research)
Subunit vaccines consisting of highly purified antigens require the presence of adjuvants to create effective and long-lasting protective immunity. Advances on adjuvant research include designing combination adjuvants which incorporate two or more adjuvants to enhance vaccine efficacy. Previously, an oil-in-water emulsion adjuvant (OW-14) composed of mineral oil and an inexpensive gum Arabic emulsifier has been reported demonstrating enhanced and robust immune responses when used as an adjuvant in swine subunit vaccines. This study presents a modified version of OW-14 prepared with food-grade Quillaja saponin extract (OWq). In new OWq emulsion, saponin extract served as an emulsifier for stabilization of emulsion droplets and as an immunoactive compound. The use of saponins allowed to reduce the required amount of emulsifier in the original OW-14. However, emulsion stabilized with saponins demonstrated extended physical stability even at elevated temperature (37°C). The two-dose vaccination with a classical swine fever virus (CSFV) glycoprotein E2-based vaccine formulated with OWq produced higher levels of E2-specific IgG and virus neutralizing antibodies in pigs in contrast with animals that received the vaccine adjuvanted with oil only. In addition, new OWq adjuvant was safe to use in the vaccination of pigs.